Identification of multisegmental nociceptive afferents that modulate locomotor circuits in the neonatal mouse spinal cord. Issue 12 (19th June 2013) - Mandadi, Sravan; Hong, Peter; Tran, Michelle A.; Bráz, Joao M.; Colarusso, Pina; Basbaum, Allan I.; Whelan, Patrick J.
ABSTRACT Compared to proprioceptive afferent collateral projections, less is known about the anatomical, neurochemical, and functional basis of nociceptive collateral projections modulating lumbar central pattern generators (CPG). Quick response times are critical to ensure rapid escape from aversive stimuli. Furthermore, sensitization of nociceptive afferent pathways can contribute to a pathological activation of motor circuits. We investigated the extent and role of collaterals of capsaicin‐sensitive nociceptive sacrocaudal afferent (nSCA) nerves that directly ascend several spinal segments in Lissauer's tract and the dorsal column and regulate motor activity. Anterograde tracing demonstrated direct multisegmental projections of the sacral dorsal root 4 (S4) afferent collaterals in Lissauer's tract and in the dorsal column. Subsets of the traced S4 afferent collaterals expressed transient receptor potential vanilloid 1 (TRPV1), which transduces a nociceptive response to capsaicin. Electrophysiological data revealed that S4 dorsal root stimulation could evoke regular rhythmic bursting activity, and our data suggested that capsaicin‐sensitive collaterals contribute to CPG activation across multiple segments. Capsaicin's effect on S4‐evoked locomotor activity was potent until the lumbar 5 (L5) segments, and diminished in rostral segments. Using calcium imaging we found elevated calcium transients within Lissauer's tract and dorsal column at L5 segments when compared to the calcium transients only within the dorsal column at the lumbar 2 (L2) segments, which were desensitized by capsaicin. We conclude that lumbar locomotor networks in the neonatal mouse spinal cord are targets for modulation by direct multisegmental nSCA, subsets of which express TRPV1 in Lissauer's tract and the dorsal column. J. Comp. Neurol. 521:2870–2887, 2013. © 2013 Wiley Periodicals, Inc.